A self-assembled peptide mimetic of a tubular host and a supramolecular polymer. Issue 2 (28th November 2016) - Paikar, Arpita; Pramanik, Apurba; Das, Tanmay; Haldar, Debasish
Abstract : A tripeptide self-assembles in a helical manner to form a tubular host-like supramolecular nanotube. The tube with a hydrophobic core has been used to develop a supramolecular polymer. Abstract : Simple and efficient strategies for the generation of a supramolecular nanotube by self-assembly of acyclic modular building blocks and guest encapsulation remain an essentially unmet challenge. A tripeptide containing leucine, Aib and serine forms a rigid type-III′ β-turn structure stabilized by multiple intramolecular N–H⋯O and O–H⋯O hydrogen bonds. The modular building blocks self-assemble in a helical manner to develop a supramolecular nanotube. The formation of a self-assembled peptide mimetic of the nanotubular host has been proven with SEM, X-ray crystallography and other spectroscopic techniques. This supramolecular nanotube with a hydrophobic core has been used as the host for modular inclusion of designer hydrophobic guests to fabricate a supramolecular polymer. The interactions between the host and the guest were analyzed by using DLS and different spectroscopic techniques. The variable temperature NMR experiments show that with the increasing temperature the hydrophobic interactions between the host and the guest decrease, which indicates the sliding of the tubular host along the guest axle. Comparison of a coumarin based guest with a naphthalenediimide based guest shows that the latter have connected two tubular hosts and thus formed a supramolecular polymer. The formation of the supramolecular polymer has been proven with DLS, SEM and AFM and other spectroscopic techniques.